낙지 Octopus minor 수컷 생식기관의 미세해부학적 구조 - 김성진; 김현진; 신소령; 서명교; 김평우; 김은하; 이정식; Seong Jin Kim; Hyeon Jin Kim; So Ryung Shin; Myeong Gyo Seo; Pyeong Woo Kim; et al. (한국해양생명과학회지, 2023)
This study was described the microscopic anatomy of male reproductive organs and spermatophore necessary for understanding the reproductive ecology of the long arm octopus Octopus minor. The long arm octopus was a species that has sexual dimorphism that can distinguish between sex based on the presence of hectocotylus. Male reproductive organs consisted of testis, primary spermatic duct, spermatic gland, secondary spermatic duct, spermatophoric gland and spermatophoric sac. Histologically, the testis was testicular tubule type and male germ cells showed a layered arrangement. The primary spermatic duct was a tube connecting the testis and spermatic gland, and consisted with epithelial layer and connective tissue. The spermatic gland was located between the primary and secondary spermatic duct, and the epithelial layer was composed of epithelial cells and mucous cells. Mucous cells reacted blue in the AB-PAS (pH 2.5) reaction and purple in the AF-AB (pH 2.5) reaction. The secondary spermatic duct was a short tube connecting spermatic gland and spermatophoric gland, and folds were developed in lumen. The spermatophoric gland consisted of numerous tubular glands and secretory cells had eosinophilic granules. The spermatophoric sac was shape of pouch, folds were developed in lumen, and vacuolar secretory cells were present in the epithelial layer. The spermatophore was 83.5 mm long and consisted of cap thread in anterior portion, ejaculatory apparatus and cement body in medial portion, sperm mass in posterior portion. 본 연구는 낙지의 생식생태 이해에 필요한 수컷 생식기관과 정포의 미세해부학적 구조를 기재하였다. 낙지는 교접완의 유무를 통하여 성을 구별할 수 있는 성적이형을 갖는 종이다. 수컷 생식기관은 정소, 일차수정관, 저정낭, 이차수정관, 정포선, 정포낭으로 구성된다. 정소는 조직학적으로 정세관형이었으며, 수컷 생식세포들은 층상배열상을 보였다. 일차수정관은 정소와 저정낭을 연결하는 관으로 상피층과 결합조직으로 이루어져 있었다. 저정낭은 일차수정관과 이차수정관의 사이에 위치하며, 상피층은 상피세포와 점액세포로 구성된다. 점액세포는 AB-PAS (pH 2.5) 반응에서 푸른색, AF-AB (pH 2.5) 반응에서 보라색으로 반응하였다. 이차수정관은 저정낭과 정포선을 연결하는 짧은 관으로 내강에 주름이 발달하였다. 정포선은 다수의 관상선으로 이루어져 있었으며, 분비세포는 호산성 과립을 가지고 있었다. 정포낭은 주머니 모양으로 내강에 주름이 발달하였으며, 상피층에 공포상의 분비세포가 존재하였다. 정포는 길이 약 83.5 mm로 전방부의 당김사, 중간부의 발사체와 고정체, 후방부의 정자 저장부로 구성되어 있었다.